The Role of Criminal Law in Reforming The Criminal Justice System: A Case Study of Handling Prison Overcrowding - Karolus Kopong Medan; Mohammad Solekha; Ade Cici Rohayati; Arief Fahmi Lubis (PT. Anagata Sembagi Education, 2025)
Overcrowding in Indonesian prisons is a structural problem in the criminal justice system that reflects the repressive nature of criminal law policy. Data from the Directorate General of Corrections (Ditjen PAS) shows that the occupancy rate of prisons exceeds 200% of the ideal capacity, violating the rights of prisoners as guaranteed in the 1945 Constitution and Law Number 12 of 1995 concerning Corrections. Overcrowding has an impact on the increase in violence, the spread of disease, and the failure of coaching programs. One of the main causes of this condition is a punishment policy that focuses too much on imprisonment without considering alternatives such as decriminalization and restorative justice. Most prisoners come from minor criminal cases, including drug abuse in the category of users who are more appropriate for rehabilitation. This policy not only burdens the state budget but also increases recidivism. Studies from various countries show that a rehabilitation-based punishment system is more effective in reducing crime. Therefore, criminal law reform through regulatory revision and the application of alternative punishment are crucial steps in overcoming overcrowding and creating a more equitable correctional system